Anti-Factor H Antibodies in Egyptian Children with Hemolytic Uremic Syndrome. (18th November 2021) - Shawky, Shereen; Safouh, Hesham; Gamal, Mona; Abbas, Mohammed M.; Aboul-Enein, Azza; Sawai, Toshihiro; Fahmy, Yosra; Selim, Heba
Abstract : Background . Atypical hemolytic uremic syndrome (aHUS) is an important cause of acute kidney injury in children. It is primarily caused by dysregulation of the complement alternative pathway due to genetic mutations, mainly in complement factor H genes, or due to anti-factor H autoantibodies (anti-FH), leading to uncontrolled overactivation of the complement system. Early diagnosis and treatment of autoimmune HUS (AI-HUS) is essential and leads to a favorable outcome. Methods . Fifty pediatric HUS patients and 50 age- and sex-matched controls were included in the study. Patients were subjected to full history taking, clinical examination, and laboratory testing. All candidates were subjected to an assessment of anti-FH in serum by a homemade enzyme-linked immunosorbent assay technique. Results . A high frequency of serum anti-FH was detected in our aHUS patients. The disease onset of AI-HUS was mainly observed in March and April, with significantly higher rates in school-aged males. All patients who started immunosuppressives early together with plasmapheresis upon detection of their anti-FH had complete renal function recovery. Conclusion . The high frequency of AI-HUS revealed in Egyptian HUS children in our study highlights the importance of implementing anti-FH testing in Egypt to provide early recognition for immediate proper management, including early immunosuppressive therapy, and hence improving patient outcomes.